Screening Corneal Tomography for the Diagnosis of Keratoconus in Pediatric Patients With Trisomy 21 - Smith, Casey G.; Edwards Mayhew, Rebecca G.; Singh, Jasleen K.; Patnaik, Jennifer L.; Wagner, Brandie D.; Wise, Ronald E.; Jung, Jennifer L.; Puente, Michael A.; Hickey, Francis; Fonteh, Cheryl; McCourt, Emily A. (American journal of ophthalmology, 2025)
•There are high rates of keratoconus in children with down syndrome (DS).•Children with DS are higher risk for complications from corneal transplant and tend to have lower contact lens tolerance.•Children with DS are candidates for a disease modifying keratoconus treatment, corneal cross-linking.•Children with DS often have lower amounts of myopia and astigmatism at the time of keratoconus diagnosis.•Screening tomography should be considered in children with DS whenever possible, as early keratoconus detection and disease modifying intervention (ie, cross-linking) can improve visual outcomes. The goal of this study is to describe the rates of successful corneal tomography in children with Down Syndrome (DS) and to determine whether high levels of astigmatism or myopia are reliable indicators of keratoconus in children with DS. Retrospective, cross-sectional study. Patients aged 4 to 18 years old with and without DS who underwent corneal tomography to evaluate for keratoconus at a tertiary pediatric hospital from July 2018-January 2020. Main observation performed was identifying keratoconus and the success of tomography in patients with down syndrome. Refractive error at the time of keratoconus diagnosis. 358 patients with DS were seen during the study period, and 96 patients without DS were evaluated for keratoconus. Among the patients with DS screened for keratoconus, useful images were obtained in at least 1 eye in 75.9% of patients. We compared patients with and without DS who were diagnosed with keratoconus or keratoconus suspect. At the time of keratoconus diagnosis, children with DS had less astigmatism and myopia than children without DS. Within the group of patients with DS, there was no significant difference in refractive error in the patients who were diagnosed with keratoconus versus those who were not. Children with DS diagnosed with keratoconus often have lower amounts of astigmatism and less myopic spherical equivalents than children with keratoconus without DS at the time of diagnosis; therefore, relying on high astigmatism as a clinical indicator for disease in patients with DS is likely inadequate. Tomographic screening should be employed even when the patient with DS is young or has low amounts of refractive error as earlier detection and treatment is crucial to favorable outcomes in children with DS.